A Numerical Procedure for the Optimization of IGBT Module Packaging - Lu, Hua; Rajaguru, Pushparajah; Bailey, Chris (2018 19th International Conference on Electronic Packaging Technology (ICEPT), 2018)
A numerical solution procedure for optimizing the thermal-mechanical reliability of an IGBT module has been described in this paper. The procedure is robust and it can handle both discrete and continuous decision variables in the design of IGBT packaging. An example has been given to demonstrate its application. The objective functions in this example are the accumulated plastic work density in solder joints of a simplified IGBT module that is subject to cyclic temperature cycling and the maximum junction temperature when the model is subject to a constant thermal loading. The thickness of the chip mount-down solder, thickness of the substrate solder joint, and the location of the chip are used as continuous decision variables. The material selection for the baseplate is treated as a discrete variable. The objective function values are calculated using Finite Element Analysis method.